2005
DOI: 10.1002/elan.200403246
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Modified Electrodes Show a Reduced Interference by Cu(II) in the Detection of As(III) Using Anodic Stripping Voltammetry

Abstract: Interference by Cu(II) causes serious problems in the detection of As(III) using anodic stripping voltammetry at gold electrodes. The behavior of Cu(II) and As(III) were examined at both a gold macro electrode and two kinds of gold nanoparticle modified electrodes, one where gold particles are deposited on glassy carbon (GC) and the other where basal plane pyrolytic graphite (BPPG) is the substrate. The sensitivity of As(III) detection was higher on gold nanoparticle modified electrodes than those on a macro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 17 publications
1
80
0
Order By: Relevance
“…In such a situation the concentration profile of species A may be simulated independently from that of species B [14].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In such a situation the concentration profile of species A may be simulated independently from that of species B [14].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…31 Dai et al have reported the synthesis of AuNPs by applying a potential step on the GC electrode immersed in acidic AuCl 4 -solution in order to use nanoparticles for the determination of As(III). 32 For this work, pencil graphite (PG) was chosen as the disposable carbon based substrate owing to its availability and cost-effectiveness. It has been used as a sorbent in solidphase microextraction of alcohols, 33 as a substrate to study nucleation mechanisms 34 and for coating polymer films by electropolymerization 35 and as an electrode for electrodeposition metals for analytic and catalytic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are Au-nanoparticle modified glassy carbon electrode (GCE), [12][13][14] Au modified boron doped diamond (BDD) electrode, 15,16 Au nanoparticle modified carbon nanotubes or carbon microspheres [17][18][19] and Au nanoelectrode ensembles. 20 Among other methods are silver electrode, 21 Platinum (Pt) nanoparticle modified GCE, 22 Pt nanotube, 23 Pt modified BDD electrode, 24 Iridium-implanted BDD electrode, 25 arsenite oxidase biosensor, 26 screen printed ring disk carbon electrode, 27 and cobalt oxide nanoparticle modified GCE.…”
mentioning
confidence: 99%